Women and the sexual division of labor: A bibliographic study on working conditions of female heads of households - Goerck , Caroline; Caetano, Sibele Lino (Seven Editora, 2024)
The focus of the article is to give visibility to the working conditions of women heads of household in the market, as well as how they relate to the double and triple shift. The specific objectives of the research are: to identify how the double/triple workday impacts the lives of female heads of household, in order to understand their realities; to investigate the representativeness of the insertion of female heads of household in the sexual division of labor, seeking to apprehend this inequality; and to find out what are the characteristics of female heads of households in the second decade of the twenty-first century. The study is qualitative in nature and was carried out by bibliographic and documentary research, exploring works, articles and statistical data. It is concluded that on the threshold of the twenty-first century, women have their insertions in the market in an unequal way in relation to men, whether in income or in professional occupations. With this reality, it was possible to understand that the sexual division of labor in our society continues to have significance. It was observed that female heads of household have a doubling or tripling of their working hours due to the services and responsibilities of the home, along with the raising and education of their children. It was found that black and brown women are the ones who experience the greatest inequalities. DOI:https://doi.org/10.56238/sevened2023.006-121